Barriers, drivers, and public support instruments on international business development among manufacturing SMEs in Finland - Yli-Viitala, Pirjo; Arrasvuori, Juha; Wathen, Pertti (University of Vaasa, 2019)
International business development is critical to manufacturing SMEs since these businesses need to extend their markets internationally in order to stay in the competition. Many barriers, drivers, and regional public support instruments influence their international business development. Appreciating these barriers, drivers, and public support instruments is core to the successful promotion of internationalization. This research aims to study the influences of various types of barriers, drivers, and public support instruments on international business development in Finland. The study draws on diverse data, including qualitative interviews with company representatives and regional innovation actors. The results showed that the barriers of ‘limited managerial information’ and ‘lack of resources’ have a significant negative influence on international business development. Furthermore, the results indicated that the drivers of ‘research, development and innovation’, ‘home government assistance’, and ‘foreign market’ have a significant positive influence on international business development. Here, various public support instruments provided by the regional innovation actors may further strengthen the drivers to overcome the barriers. In addition to the empirical contribution, the article highlights the dynamics between the barriers, drivers and public support instruments, and suggests that national policymakers, regional innovation actors and SMEs should further strengthen what drives SMEs’ international business development to indirectly mitigate the barriers.
Keywords: SC-research